A primer-test centered equating method for setting cut-off scores - Zhu, W.; Plowman, S. A.; Park, Y. (Research Quarterly for Exercise and Sport, 2010)
This study evaluated the use of a new primary field test method based on test equating to address inconsistent classification among field tests. We analyzed students' information on the Progressive Aerobic Cardiovascular Endurance Run (PACER), mile run (MR), and VO2max from three data sets (college: n = 94; middle school: n = 39; elementary school: n = 96). Using the college and elementary school data, the equivalent relationship between PACER and MR scores was first established by the Kernel equating method. This yielded MR scores derived from PACER (mile run PACER equated [MR PEQ]), which were used to predict maximal oxygen uptake (VO2max) and classify students according to the FITNESSGRAM® Healthy Fitness Zones™. We compared the results to the predictions and classifications based on measured VO2max, MR, and PACER-predicted VO2max and cross-validated the relationships using the middle school data. We found the test conversion to be accurate and that the MR PEQ scores functioned similarly to the original MR scores. Both performed better than the original PACER scores in predicting VO2max and classifying students. The middle school data generally supported these results. The proposed method is accurate and effective in setting a new field test onto the same scale of a primary field test and determining its cut-off scores.